PENGARUH PROFITABILITAS, LIKUIDITAS, UKURAN PERUSAHAAN, INTENSITAS PERSEDIAAN, DAN PERTUMBUHAN PENJUALAN PADA AGRESIVITAS PAJAK - Ningsih, Ni Putu Meiditya; Noviari, Naniek (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.09.TAHUN.2022DO - 10.24843/EEB.2022.v11.i09.p04, 2022)
The purpose of this study was to obtain empirical evidence of the effect of profitability, liquidity, firm size, inventory intensity, and sales growth on the tax aggressiveness of manufacturing companies listed on the Indonesia Stock Exchange for the period 2016 – 2020. This study was conducted on manufacturing companies listed on the Indonesia Stock Exchange. 2016 – 2020. The method of determining the sample used is using the non-probability sampling method with purposive sampling technique. There are 122 sample companies with a total of 610 observations. The data used were then analyzed using multiple linear regression. The results showed that profitability had a positive effect on tax aggressiveness. Liquidity has a positive effect on tax aggressiveness. Firm size has a positive effect on tax aggressiveness. Inventory intensity and sales growth have no effect on tax aggressiveness. The implication of this research is that it is expected to contribute and refer to further research on the effect of profitability, liquidity, firm size, inventory intensity, and sales growth on tax aggressiveness. In addition, it is hoped that the government can minimize fraud and fraud by companies.